Formation of the Bovine Ovarian Surface Epithelium during Fetal Development. (February 2020) - Hartanti, Monica D.; Hummitzsch, Katja; Bonner, Wendy M.; Bastian, Nicole A.; Irving-Rodgers, Helen F.; Rodgers, Raymond J.
When first formed, the ovary only has an established epithelium at its base or hilum. Later, an epithelium is established around the rest of the ovary. To examine this further, we conducted scanning electron microscopy of the surface of bovine fetal ovaries and immunohistochemistry of ovarian cross-sections. From the earliest time point, the cells on the surface of the base or hilum of the ovary were cuboidal. On the remainder of the ovary, the surface was more irregular. By mid-development, the surface was covered completely with either a stratified or simple epithelium of cuboidal cells. Clefts were observed in the surface and appeared to form due to the expansion of stroma surrounding each open ovigerous cord, elevating the areas surrounding each cord, while leaving the opening of the cord to form the base of each cleft. The continued expansion of the surrounding stroma below the surface appeared not only to close the ovigerous cords from the surface but to compress the clefts into the shape of a groove. Later, most of the ovarian surface was covered with a simple cuboidal epithelium. The changes to the ovarian surface during fetal development coincide with the remodeling of the stroma and cords below.